IDENTIFICATION OF FACTORS CONTROLLING THE QUALITY OF GROUNDWATER IN MITIDJA PLAIN USING INDEXING METHOD AND STATISTICAL ANALYSIS - Zamiche, S.; Hamaidi-Chergui, F.; Demiai, A.; Belaidi, M. (University of Eloued جامعة الوادي, 2018)
In this paper, we describe the hydro geochemical processes in the aquifer of Mitidja using hydro chemical data, statistical analysis and Water Quality Index (WQI) to identify evidence of contamination processes. Two factors were found that explained hydro chemical evolution in the aquifer. These factors reveal the existence of an intrusion of seawater and mechanisms of nitrate contamination of groundwater. The effect of each parameter on the WQI show that the highest mean effective weight value belongs to the TDS, NO3- and SO42- parameters. These results indicated that natural and anthropogenic activities are responsible for the degrading of groundwater quality in the Mitidja plain.
Article in Journal of Fundamental and sciences. university of el oued
Keywords: Aquifer of Mitidja; Hydro geochimistry; Nitrate contamination; intrusion of seawater; WQI.